A putative curved DNA region upstream of rcsA in Escherichia coli plays a key role in transcriptional regulation by H‐NS. Issue 8 (26th June 2018) - Meenakshi, Shanmugaraja; Karthik, Maruthan; Munavar, M. Hussain
Abstract : It is well established that in Escherichia coli, the histone‐like nucleoid structuring (H‐NS) protein also functions as negative regulator of rcsA transcription. However, the exact mode of regulation of rcsA transcription by H‐NS has not been studied extensively. Here, we report the multicopy effect of dominant‐negative hns alleles on the transcription of rcsA based on expression of cps‐lac transcriptional fusion in ∆ lon, ∆ lon rpoB12, ∆ lon rpoB77 and lon + strains. Our results indicate that H‐NS defective in recognizing curved DNA fails to repress rcsA transcription significantly, while nonoligomeric H‐NS molecules still retain the repressor activity to an appreciable extent. Together with bioinformatics analysis, our study envisages a critical role for the putative curved DNA region present upstream of rcsA promoter in the transcriptional regulation of rcsA by H‐NS. Abstract : The histone‐like nucleoid structuring (H‐NS) protein affects gene expression in bacteria in different ways. It has been shown to negatively regulate rcsA transcription, but the mode of regulation still remains to be elusive. By employing clones bearing dominant‐negative alleles of hns, together with bioinformatics analyses, we have predicted a putative curved DNA region upstream of rcsA promoter which might play a key role in the regulation of rcsA transcription by H‐NS.